Potential clusters for joint village land use planning in Mvomero District, Morogoro Region - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing potential clusters of villages for joint village land use planning as defined by the Sustainable Rangeland Management project in Mvomero District, Morogoro region, Tanzania.